Rancang Bangun Website Sistem Informasi Pemesanan Desain Interior Dan Eksterior Perkantoran - Dedeh Supriyanti; Ariq Firmusetia Putra; Muhammad Taufan Gunasri (UNIVERSITAS RAHARJA, 2022)
With the rapid development of technology, business competition is getting tougher in the company, thus encouraging the emergence of new innovations to meet the needs of companies with technology that is able to support all work activities quickly and accurately. The ongoing business process at Onna Kreasi Aesthetics is semi-computerized in recording sales transactions, thus hampering the smooth running of reports. The purpose of this research is to analyze the company's ongoing business processes, provide recommendations and design a sales information system that can support the company's operations. The PIECES analysis method is used in this study, UML is used to describe or describe the running system and the system proposed in this study. Black box testing is used to find out whether the system created is running well or not. This research produces a system that can facilitate transaction data collection, and is reliable. Proving results that the system created can help the company's performance in carrying out ordering activities, and monitoring sales so that business processes can run faster and ensure accurate and quality data sources.